2019
DOI: 10.1038/s41467-019-08871-1
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow central memory and memory stem T-cell exhaustion in AML patients relapsing after HSCT

Abstract: The major cause of death after allogeneic Hematopoietic Stem Cell Transplantation (HSCT) for acute myeloid leukemia (AML) is disease relapse. We investigated the expression of Inhibitory Receptors (IR; PD-1/CTLA-4/TIM-3/LAG-3/2B4/KLRG1/GITR) on T cells infiltrating the bone marrow (BM) of 32 AML patients relapsing (median 251 days) or maintaining complete remission (CR; median 1 year) after HSCT. A higher proportion of early-differentiated Memory Stem (TSCM) and Central Memory BM-T cells express multiple IR in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
152
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(162 citation statements)
references
References 51 publications
9
152
1
Order By: Relevance
“…The exhausted BM-T cell phenotype was associated with a restricted TCR repertoire, impaired effector functions and leukemia-reactive specificities. Furthermore, early detection of severely exhausted BM-memory stem T cells predicted relapse (202). Interestingly, IR-positive T cells infiltrating the BM of AML patients at relapse displayed a greater ability to recognize matched leukemic blasts after in vitro expansion compared with their IR-negative counterparts.…”
Section: Relapse and Immune Evasion Mechanisms After Haplo-hctmentioning
confidence: 99%
See 1 more Smart Citation
“…The exhausted BM-T cell phenotype was associated with a restricted TCR repertoire, impaired effector functions and leukemia-reactive specificities. Furthermore, early detection of severely exhausted BM-memory stem T cells predicted relapse (202). Interestingly, IR-positive T cells infiltrating the BM of AML patients at relapse displayed a greater ability to recognize matched leukemic blasts after in vitro expansion compared with their IR-negative counterparts.…”
Section: Relapse and Immune Evasion Mechanisms After Haplo-hctmentioning
confidence: 99%
“…Interestingly, IR-positive T cells infiltrating the BM of AML patients at relapse displayed a greater ability to recognize matched leukemic blasts after in vitro expansion compared with their IR-negative counterparts. This suggest that IR expression marks lymphocytes enriched for tumor specificity whose activity could be unleashed with therapeutic check-point blockade, although innovative targeted strategies will be required to avoid exacerbation of GVHD in the HCT context (202).…”
Section: Relapse and Immune Evasion Mechanisms After Haplo-hctmentioning
confidence: 99%
“…Further studies are needed to understand the durability of these responses, whether dosing can be adjusted to improve the safety profile while retaining efficacy, and how patientsʼ prior GVHD prophylaxis might impact their risk of GVHD. In AML patients, Noviello et al have demonstrated that the detection of severely exhausted (PD‐1 + Eomes + T‐bet − ) T cells in the bone marrow shortly after transplant predicts relapse . This finding suggests the possibility that intervention with immune checkpoint inhibitors could be used to prevent relapse in patients with early evidence of T cell exhaustion following transplant, but the aforementioned safety concerns currently limit the appeal of such an approach.…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 99%
“…Interestingly, these patients also have a greater number of early-differentiated memory stem T cells and central memory T cells with multiple inhibitory receptors than those of patients who remain in CR. Moreover, relapse is effectively predicted by the early identification of BM memory stem T cells displaying a severely exhausted phenotype (PD1+, Eomes+, T-bet-) [14].…”
Section: Immune-checkpoint Receptors and Co-inhibitor Receptorsmentioning
confidence: 99%
“…Currently, the relevance of this tight interaction has been further substantiated by the demonstration that post-transplant AML relapse is not caused by the development of additional genetic alterations as in patients relapsing after chemotherapy [8], but by the loss or down-regulation of major histocompatibility (MHC) class II genes [9,10]. This seminal finding has paved the way for identifying and revealing other novel potential mechanisms of immune escape that are operative not only in the transplant setting [11][12][13][14], but also in the chemotherapy setting [15,16]. Notably, clarifying studies on these immune escape mechanisms have allowed the development of targeted immunotherapies, which are already providing promising results [11,17].…”
Section: Introductionmentioning
confidence: 99%